2015
DOI: 10.4314/jasem.v19i1.6
|View full text |Cite
|
Sign up to set email alerts
|

Biofilm formation of <i>Salmonella</i> species isolated from fresh cabbage and spinach

Abstract: ABSTRACT:The aim of the study was to isolate Salmonella from fresh cabbage and spinach vegetables, determine antimicrobial resistance and biofilm formation of the isolates. Spinach and cabbage farm vegetables were found to harbour Salmonella. A total of eighty-two Salmonella isolates were recovered from both vegetables and subjected to antimicrobial reactions. Salmonella isolate showed sensitivity against the aminoglycoside and quinolones.Isolates from cabbage showed ≥ 80% susceptibility to nalidixic acid and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 27 publications
4
4
0
Order By: Relevance
“…While, 5/6 (83.3%) resistant to Ampicillin (10 µg), 3/6 (50%) were resistant to Amoxicillin (25 µg), and 1/6 (16.7%) resistant to Chloramphenicol (30 µg). this results agree with [25] who found that a variable resistant patterns was observed for tetracycline (58%:47%), ampicillin (55.5%:31.4%), erythromycin (58.1%:62.7%), streptomycin (64.5%:76.5%), cephalothin (35.5%:39.2%) against Salmonella isolated from cabbage and spinach respectively and agree with a study done by [26] which showed a high resistance of Salmonella spp isolated from lettuce samples toward amoxicillin/ clavulanic-acid or ampicillin.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…While, 5/6 (83.3%) resistant to Ampicillin (10 µg), 3/6 (50%) were resistant to Amoxicillin (25 µg), and 1/6 (16.7%) resistant to Chloramphenicol (30 µg). this results agree with [25] who found that a variable resistant patterns was observed for tetracycline (58%:47%), ampicillin (55.5%:31.4%), erythromycin (58.1%:62.7%), streptomycin (64.5%:76.5%), cephalothin (35.5%:39.2%) against Salmonella isolated from cabbage and spinach respectively and agree with a study done by [26] which showed a high resistance of Salmonella spp isolated from lettuce samples toward amoxicillin/ clavulanic-acid or ampicillin.…”
Section: Discussionsupporting
confidence: 91%
“…In the present study all six Salmonella isolates (100%) showed sensitivity toward Amikacin (30 µg), Ciprofloxacin (5 µg), Doxycycline (30 µg), Gentamicin (10 µg), Norfloxacin (10 µg), Streptomycin (10 µg), Tetracycline (30 µg) followed by chloramphenicol (30 µg) (5/6, 83.3%,), amoxicillin 25 µg (5/6, 33.3%), this results agree with the findings of [25], who found that all Salmonella isolates that recovered from vegetables and subjected to antimicrobial reactions were sensitive toward the aminoglycoside and quinolones. Isolates from cabbage showed.…”
Section: Discussionsupporting
confidence: 87%
“…While 5/6 (83.3%) resistant to Ampicillin (10 µg), 3/6 (50%) were resistant to Amoxicillin (25 µg), and 1/6 (16.7%) resistant to Chloramphenicol (30 µg). this results agree with [25] who found that a variable resistant patterns was observed for tetracycline (58%:47%), ampicillin (55.5%:31.4%), erythromycin (58.1%:62.7%), streptomycin (64.5%:76.5%), cephalothin (35.5%:39.2%) against Salmonella isolated from cabbage and spinach respectively and agree with a study done by [26] which showed a high resistance of Salmonella spp isolated from lettuce samples toward amoxicillin/ clavulanicacid or ampicillin.…”
Section: Discussionsupporting
confidence: 91%
“… Malangu and Ogunbanjo (2009) reported an acute Salmonella poisoning in 2005 emanating from South African Hospitals. Biofilm production was reported in drinking water ( Mulamattathil et al 2014 ), while Isoken (2015) reported the isolation of biofilm-forming Salmonella species in cabbage and spinach sold in South Africa. The presence of Salmonella species in food and water provides opportunities for cross-contamination along the food chain and accounts for diseases in susceptible individuals ( Karkey et al 2016 ; Byrd-Bredbenner, 2017 ).…”
Section: Introductionmentioning
confidence: 99%